Intervention of Nitrogen Evolution on Species Diversity of Broad-leaved Forest Plants in Xianweng Mountain. Issue 3 (February 2020) - Chang, Wenbo; Sun, Yanbin; Shen, Penglin; Chen, Qingsong; Miao, Tianlin; Li, Lan
Abstract: Nitrogen evolution is one of the important factors driving biodiversity change. It is generally believed that the species diversity structure will be changed, and under the conditions of exogenous nitrogen addition, grasses and deciduous shrubs have a competitive advantage over hybrid grasses and evergreen shrubs. For the competition between plants in the same life type, the interaction between different life-type plants is not involved. Therefore, from the changes in forest ecosystem structure and nitrogen elements, the response of different life-type plants to nitrogen evolution can be further explored. The lower plant species of the deciduous broad-leaved forest-Mongolian carp are studied, and different gradients of nitrogen (0, 40, 80, 120 kg N·ha − 1·yr − 1) are added to the four gradients of extraneous nitrogen effects of nitrogen evolution on forest biodiversity in the north temperate zone. The results of five-year continuous nitrogen addition experiments showed that nitrogen addition significantly reduced the species richness and diversity of understory plants, and changed the species composition of the community. Nitrogen addition increased the species richness of shrub plants and diversity, reduced the richness of herbaceous plants, and reduced the important value of grasses and increased the important value of hybrid grasses. The study showed that long-term nitrogen addition significantly changed the species composition of understory plants, and the response of different life-type plants to nitrogen addition was also different.